Ecological resilience in lakes and the conjunction fallacy. Issue 11 (November 2017) - Spears, Bryan; Futter, Martyn; Jeppesen, Erik; Huser, Brian; Ives, Stephen; Davidson, Thomas; Adrian, Rita; Angeler, David; Burthe, Sarah; Carvalho, Laurence; Daunt, Francis; Gsell, Alena; et al.
Abstract There is a pressing need to apply stability and resilience theory to environmental management to restore degraded ecosystems effectively and to mitigate the effects of impending environmental change. Lakes represent excellent model case studies in this respect and have been used widely to demonstrate theories of ecological stability and resilience that are needed to underpin preventative management approaches. However, we argue that this approach is not yet fully developed because the pursuit of empirical evidence to underpin such theoretically grounded management continues in the absence of an objective probability framework. This has blurred the lines between intuitive logic (based on the elementary principles of probability) and extensional logic (based on assumption and belief) in this field. Lake ecosystems have provided much of the empirical evidence for ecological resilience theory. Here, a more rigorous logical approach is called for when translating this research into management decisions.